Linking communities of practice with learning communities in computer science education - Hinkelmann, Knut (2006)
MoKEx (Mobile Knowledge Experience) is an international project in cooperation with universities and industrial partners. The project focuses on didactical, organizational and technical problems with regard to blended learning and knowledge management scenarios. In a project-based learning approach students of two different universities are being prepared for their future work. They are working on real-world problems in an interdisciplinary team and are collaborating within a geographically and temporally separated team. Therefore means for communication and collaboration over the Internet must be provided. From the didactical perspective the aspects of autodidactic education and team learning are playing an important role, while teachers are acting primarily as coaches. In the meantime the results of the first execution of the project have been enhanced and put into operation by the companies and a second execution has been started.